2013
DOI: 10.5271/sjweh.3356
|View full text |Cite
|
Sign up to set email alerts
|

Working hours and depressive symptomatology among full-time employees: Results from the fourth Korean National Health and Nutrition Examination Survey (2007–2009)

Abstract: We found an association between long working hours and depressive symptomatology. The full-time employees who worked long hours showed higher prevalence of depressive symptomatology after the data were adjusted for individual characteristics, socioeconomic factors, health behaviors, and work schedules. Affiliation 515Original article Scand J Work Environ Health. 2013;39(5):515-520. doi:10.5271/sjweh.3356 Working hours and depressive symptomatology among full-time employees: Results from the fourth Korean N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 13 publications
(15 reference statements)
7
42
0
Order By: Relevance
“…The effect due to selection bias may not be significant, because the proportion of control participants working long hours did not differ greatly from nationally representative data. The proportions of workers who worked more than 48 hours per week were 37 and 42.4% based on the Korean Working Conditions Surveys of 2006 and 2010, respectively, and 29.5% worked more than 52 hours according to the fourth Korean National Health and Nutrition Examination Survey (2007−2009) 28,29) . In this study, the proportions of controls who worked more than 48 hours or 52 hours was 39.9 and 26.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The effect due to selection bias may not be significant, because the proportion of control participants working long hours did not differ greatly from nationally representative data. The proportions of workers who worked more than 48 hours per week were 37 and 42.4% based on the Korean Working Conditions Surveys of 2006 and 2010, respectively, and 29.5% worked more than 52 hours according to the fourth Korean National Health and Nutrition Examination Survey (2007−2009) 28,29) . In this study, the proportions of controls who worked more than 48 hours or 52 hours was 39.9 and 26.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because this limit does not include overtime work performed on holidays, work hours in Korea may be substantially longer. Kim et al reported that the average Korean employee spends 48.57 hours a week in the workplace, that 20.72% of the employed work more than 60 hours a week and that working more than 60 hours a week is associated with increased health problems 32) . A study on healthcare staff in Japan also showed that the risks of both physical aggression and verbal abuse were significantly higher in workers with long working hours 25) .…”
Section: Discussionmentioning
confidence: 99%
“…After controlling for age, marital status, education, income, type of employment contract, night shift work, occupation, company size, and number of hours worked per week, weekend work was associated with depressive symptoms in both males and females. An explanation for the elevated ORs of depressive symptoms in weekend workers might be physical/ psychological workload and lack of recovery time (Kim et al, 2013a;Virtanen et al, 2011) because weekend work is closely linked with long working hours in Korea. In support of this hypothesis, the OR for depressive symptoms in males was decreased in multiple logistic regression model 2, which controlled for the number of hours worked per week, compared with the OR in model 1.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial work characteristics as risk factors for depression or depressive symptoms have been studied extensively in the work environment (Bonde, 2008). Besides work-related psychosocial factors, several studies have reported associations between working hours or shiftwork and depressive symptoms (Driesen et al, 2010(Driesen et al, , 2011Kim et al, 2013a;Virtanen et al, 2011). However, to our knowledge, the impact of weekend work on mental health has not been studied.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation